Data quality and uncertainty assessment of life cycle inventory data for composites - Balcioglu, Gulizar; Fitzgerald, Amy M.; Rodes, Ffion A. M.; Allen, Stephen R. (ELSEVIER SCI LTD, 2025)
Life Cycle Assessment (LCA) is an increasingly common method for assessing the environmental impact of products. For both novel and established composite materials, the quality and uncertainty of LCA data varies across sources, and there is a particular paucity of data for novel materials which can inhibit their adoption in favour of more established materials. After reviewing available LCA datasets for the constituent materials of composites, this study analyses life cycle greenhouse gas emissions datasets for a sample of materials - glass fibre, carbon fibre, and epoxide resin - and assesses the data quality and uncertainty across their sources. The results revealed major discrepancies in the datasets for the production of composites are summarised and presented via a colour-coded visual to aid interpretation and transparently select the most appropriate dataset for the LCA. The study highlights the importance of giving more attention to composite datasets in the future and advises that the process of selecting the most representative values should be approached with caution.
Keywords: A. Glass fibres; A. Carbon fibre; A. Polymer-matrix composites (PMCs); Life cycle assessment; Data quality; Uncertainty analysis; Engineering; Materials Science